Sistem Informasi Hasil Panen Kelapa Sawit pada Tirta Agung Estate Berbasis Web - Pakpahan, Sorang; Sinaga, Sylvia Bernadette; Rikki, Alex; Sagala, Masdiana (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2023)
In the current era of globalization, information technology is advancing rapidly. Computers are equipment created to make human work easier, while achieving progress in both hardware and software production. Tirta Agung Estate really needs an information system that supports and makes it easy to collect data on oil palm harvests. Tirta Agung Estate is a company operating in the plantation sector, especially palm oil, which is based in the city of Palembang and has its address at Jl. Margo Mulyo, District. Bayung Lencir, Musi Banyuasin Regency. Tirta Agung Estate has two work areas, namely in the field and in the factory. So far, harvest data is still recorded manually without using a website. In practice, the recapitulation process is still experiencing delays due to the lack of an integrated and computerized system, so researchers want to design a system that can facilitate ongoing business activities.